INFLUENCE OF BLOOD METABOLITES AND METABOLIC HORMONES ON POSTPARTUM OVARIAN ACTIVITY IN COWS - ALl, SARFRAJ; AWASTHl, M K; KHAN, J R; TIWARl, R P; POYAM, M R (The Indian Journal of Animal Reproduction, 2023)
Present investigation was conducted to study the influence of blood metabolites and metabolic hormones onpostpartum ovarian cyclic activity in Sahiwal cows. Selected experimental animals (n=18) had normal calving andsubsequent normal genital health without apparent history of postpartum metritis and endometritis as assessedby gynaeco-clinical examination. Blood samples were collected from each experimental animal on days 50 and60 postpartum; and blood glucose and serum concentrations of non-esterified fatty acid (NEFA), insulin,triiodothyronine (T3), thyroxin (T4) and progesterone (P4) were determined. Animals were classified as cyclic (P4 >1 ng/ml) and acyclic (P4 < 1 ng/ml) based on serum progesterone concentration on day 50 and /or day 60postpartum. An increasing trend of serum progesterone concentration was observed in both cyclic and acyclicanimals with increasing postpartum interval though extent of which was greater in cyclic animals. Non-significantdifferences were observed in blood glucose concentration, serum T3 and T4 concentrations between cyclic andacyclic animals on days 50 and 60 postpartum. Acyclic animals recorded significantly higher (P
Keywords: Postpartum cows; Blood glucose; Insulin; Triiodothyronine; Thyroxin; Progesterone